Analysis of the Deep Learning Approach in Arts, Culture and Crafts Subjects for Fourth-Grade Elementary School - Eka Dela Puspita; Andi Imrah Dewi; Kadek Hariana; Zulnuraini; Andi Rahmaeni (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to describe the implementation of the deep learning approach and identify supporting and inhibiting factrors in the Arts, Culture, and Crafts (SBdP) subject in class IV A of SD Negeri 5 Palu. This study uses a qualitative approach with descriptive methods. The research subjects consisted of class IV A teachers and 23 students. Data collection was carried out through observation, interviews, and documentation, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results show that the deep learning approach has been implemented through the principles of meaningful learning, mindful learning, and joyful learning. The teacher links the material to students’ real experiences, facilitates reflection activities, and creates an active and enjoyable learning atmosphere through discussions, practices, educational games, and ice breakers. This implementation shows that the indicators of the deep learning approach have been met in the SBdP learning process and are able to increase student engagement, creativity, and understanding. However, in the reflection aspect, some students are still unable to explain in depth the process and learning outcomes obtained. Supporting factors for implementing a deep learning approach include teacher competence, a conducive learning environment, and adequate school facilities, while inhibiting factors include differences in student abilities and limited learning time. Thus, a deep learning approach can support the creation of meaningful learning, conscious, and enjoyable Arts and Culture learning in elementary school.